2020
DOI: 10.1002/cpe.5693
|View full text |Cite
|
Sign up to set email alerts
|

Performance evaluation of containers and virtual machines when running Cassandra workload concurrently

Abstract: SummaryNoSQL distributed databases are often used as Big Data platforms. To provide efficient resource sharing and cost effectiveness, such distributed databases typically run concurrently on a virtualized infrastructure that could be implemented using hypervisor‐based virtualization or container‐based virtualization. Hypervisor‐based virtualization is a mature technology but imposes overhead on CPU, networking, and disk. Recently, by sharing the operating system resources and simplifying the deployment of app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…A slightly similar performance investigation of multiple instances of VMWare VMs and Docker containers running concurrently, albeit in the context of multiple instances of a Cassandra database running concurrently was presented in paper [7]. Firstly, for one Cassandra cluster, the authors showed averaged latency of 1.35 ms for Docker vs. 1.9 ms VMWare and 1.2 non-virtualized for replication factor 1, 1.9 ms, 4.4 ms and 2.1 ms for replication factor 2 and 2.2 ms, 5.45 ms and 2.1 ms for replication factor 3 for Docker, VMWare and the non-virtualized environment, respectively.…”
Section: Related Work and Motivationmentioning
confidence: 93%
See 2 more Smart Citations
“…A slightly similar performance investigation of multiple instances of VMWare VMs and Docker containers running concurrently, albeit in the context of multiple instances of a Cassandra database running concurrently was presented in paper [7]. Firstly, for one Cassandra cluster, the authors showed averaged latency of 1.35 ms for Docker vs. 1.9 ms VMWare and 1.2 non-virtualized for replication factor 1, 1.9 ms, 4.4 ms and 2.1 ms for replication factor 2 and 2.2 ms, 5.45 ms and 2.1 ms for replication factor 3 for Docker, VMWare and the non-virtualized environment, respectively.…”
Section: Related Work and Motivationmentioning
confidence: 93%
“…We can note that, the best speed-up for DAC and Host is reached using 256 processes (oversubscription) although it is very close to 64 and 128 process configurations, for DAC and Docker it is best for 64 processes; for MasterSlave, using 64 processes; and SPMD-128 processes and falling afterwards. Speed-up was calculated using function (7). speedup(mach, param, prog, proc) = medianExecutionTime(mach, param, prog, 1) medianExecutionTime(mach, param, prog, proc) We shall note that we generally expect a decrease in execution time with an increasing number of processes assuming these run on separate physical or logical cores in the system, in our case 64 and 128 respectively, because such a scenario allows shortening the computational phase.…”
Section: Spmd O3_nativementioning
confidence: 99%
See 1 more Smart Citation
“…For orchestrating virtualized applications and services, containers are preferred over virtual machines (VMs) as they are lightweight [26,65] and have low startup times [19]. Kubernetes (K8s) [27] is the most popular open source container orchestration system [21].…”
Section: Containers and Kubernetesmentioning
confidence: 99%
“…In [ 21 ], the authors compared two orchestration tools and showed that Docker Swarm outperformed Kubernetes in resource usage and performance efficiency on a Raspberry Pi 3 cluster. In [ 22 ], they compared container-based Cassandra instances over virtual machines. The authors in [ 23 ] used YCSB to evaluate the Cassandra database on a Raspberry Pi 2 cluster.…”
Section: Related Workmentioning
confidence: 99%